In vitro shoot micro propagation of medicinal applications and ornamental value of Cestrum nocturnum L. - Sarkar, Mohammad Khairul Islam; Jahan, Miskat Ara Akhter; Roy, Chapol Kumar; Hossain, Khaled; Rahman, Shafkat Shamim; Mia, Md Rubel; Islam, Mohammad Rafiqul; Azim, Dewan Anwarul (© 2016 Indian Society for Education and Environment, 2016)
This article was published in the Indian Journal of Science and Technology [© 2016 Indian Society for Education and Environment ] and the definite version is available at : http://doi.org/10.17485/ijst/2016/v9i15/86233 The Journal's website is at: http://www.indjst.org/index.php/indjst/article/view/86233